Organizational sensory systems of Polish enterprises in the context of cooperative relationships = Organizacyjne systemy sensoryczne polskich przedsiębiorstw w kontekście relacji kooperacyjnych - Chomicki, Michał (Zielona Góra: Faculty of Economics and Management Press)
The aim of this paper is to indicate the relationship between the shape of organizational sensory systems of Polish companies and beneficialness of the shape of cooperative relations between these companies with particular kinds of cooperators.
Keywords: przedsiębiorstwo; organizacja; system sensoryczny; monitoring środowiska; monitoring wewnętrzny; powiązania kooperacyjne; organizational; sensory system; environmental monitoring; internal monitoring; cooperative relationships